Efecto del fertirriego en el cultivo de pimiento (capsicum annum l.) bajo dos sistemas de riego en invernadero - Vega Saca, Laura Johanna; Zambrano Savinovich, Jorge Jossue (Machala : Universidad Técnica de Machala, 2024)
The present research work was carried out in the area of the Santa Inés Experimental Farm, which belongs to the Universidad técnica de Machala, province of El Oro, from November 2023 to January 2024. Ecuador is a mostly agricultural country with a semiarid climate, facing the challenge of optimizing the use of water in agriculture. With about half of the irrigated area actually being irrigated, the need to increase agricultural production to meet the demand of a growing population is evident.Fertigation is presented as an advanced technique that merges fertilization and irrigation,improving the efficiency of nutrient use, particularly in the cultivation of peppers. In the South American context, pepper production in Ecuador and other countries stands out, although the lack of significant advances in research and technological development in this area poses challenges. Greenhouses are emerging as key tools for optimising growing conditions, offering maximum yields and protection against pests and diseases. Adapting the frequency of irrigation according to the method used, considering factors such as soil type, climate and water losses between periods, is an essential practice in the management of water resources. The aim of this experiment was to test the effect of fertigation on morphoagronomic parameters of pepper cultivation under greenhouses. The experimental design to be used was a completely randomized complete factorial experiment (EFCCA) without fractionation, with three replications, two irrigation systems: drip and micro-sprinkler. The variables that were evaluated in the study are the following: Plant height (cm), number of fruits per plant, fruit weight (g), fruit length (cm), fruit diameter (mm) and yield (kg/ha). Irrigation is carried out every two days in treatment 1 and every four days in treatment 2, taking into account the needs of the crop. The research highlights the crucial influence of irrigation frequency on pepper cultivation. It is evident that the drip irrigation system with an interval of 2 days (T1) favors the growth of the plants, resulting in greater height and a significant number of fruits per plant (average of 9 fruits). In addition, when compared to the micro-sprinkler system (T2), it is shown that the drip irrigation system outperforms in several aspects, including weight, length and diameter of the fruit. The yield results support the effectiveness of the drip irrigation system, with significantly higher yield compared to the micro-sprinkler system. These findings confirm the hypothesis that the frequency and type of irrigation system directly impact the productivity of the pepper crop under greenhouses.
El presente trabajo de investigación se llevó a cabo en el área de la Granja Experimental Santa Inés, que pertenecen a la Universidad Técnica de Machala, provincia del El Oro, comprendido en el periodo noviembre de 2023 a enero de 2024. Ecuador es un país mayoritariamente agrícola con un clima semiárido, enfrenta el desafío de optimizar el uso del agua en la agricultura. Con aproximadamente la mitad de la superficie destinada al riego siendo efectivamente regada, la necesidad de incrementar la producción agrícola para satisfacer la demanda de una población en crecimiento es evidente. La fertirrigación se presenta como una técnica avanzada que fusiona la fertilización y el riego, mejorando la eficiencia del uso de nutrientes, particularmente en el cultivo de pimientos. En el contexto sudamericano, la producción de pimientos en Ecuador y otros países se destaca, aunque la falta de avances significativos en investigación y desarrollo tecnológico en este ámbito plantea desafíos. Los invernaderos emergen como herramientas clave para optimizar las condiciones de cultivo, ofreciendo rendimientos máximos y protección contra plagas y enfermedades. Adaptar la frecuencia de riego según el método empleado, considerando factores como el tipo de suelo, el clima y las pérdidas de agua entre periodos, se presenta como una práctica esencial en la gestión del recurso hídrico. El objetivo de este experimento fue comprobar el efecto del fertirriego en parámetros morfoagronómicos del cultivo de pimiento bajo invernadero. El diseño experimental a usar fue un experimento factorial completo completamente al azar (EFCCA) no fraccionado, con tres repeticiones, dos sistemas de riego: goteo y microaspersión. Las variables que se evaluaron en el estudio son las siguientes: Altura de planta (cm), número de frutos por planta, peso del fruto (g), longitud del fruto (cm), diámetro del fruto (mm) y rendimiento (kg/ha). El riego se realiza cada dos días en el tratamiento 1 y cada cuatro días en el tratamiento 2, tomando en cuenta las necesidades del cultivo. La investigación destaca la influencia crucial de la frecuencia de riego en el cultivo de pimiento. Se evidencia que el sistema de riego por goteo con un intervalo de 2 días (T1) favorece el crecimiento de las plantas, resultando en mayor altura y un significativo número de frutos por planta (promedio de 9 frutos). Además, al comparar con el sistema de microaspersión (T2), se demuestra que el sistema de riego por goteo supera en varios aspectos, incluyendo peso, longitud y diámetro del fruto. Los resultados de rendimiento respaldan la eficacia del sistema de riego por goteo, con un rendimiento significativamente mayor en comparación con el sistema de microaspersión. Estos hallazgos confirman la hipótesis de que la frecuencia y el tipo de sistema de riego impactan directamente en la productividad del cultivo de pimiento bajo invernadero.
Keywords: SISTEMAS DE RIEGO; FERTIRRIEGO; INTERVALOS